Menyoal Peran dan Fungsi Masjid Pemerintah Studi atas Masjid Agung Syuhada Polewali Mandar Sulawesi Barat - Husnul Fahimah Ilyas (International Journal Ihya' 'Ulum al-Din, 2015)
This policy genre study aims to identify the management, the function and the role of Great Mosque Syuhada in Polewali Mandar. It will also describe the physical condition and historical building of the mosque. The conducted qualitative research was based on interview, observation, document, and literature. The findings of the research show that the position of the grand mosque is assumed to be a representative mosque at the district level, and the provincial-level mosque that serves as a model of service and management that meets the standards, but the facts on the ground show that the management system and its management are still below the standard, which does not meet the standards imposed by the directorate of religious affairs of Islam and syariah. The roles and functions played by the Great Mosque or Masjid Agung Syuhada was limited to regular worship services, recitation, and implementation of great days of Islam.--- Penelitian ini bertujuan untuk mengetahui pengeloaan, fungsi, dan peran masjid Agung Syuhada sebagai masjid kabupaten Polewali Mandar, serta mendeskripsikan kondisi fisik dan sejarah pembangunan masjid tersebut. Penelitian kualitatif yang dilakukan berdasarkan pada wawancara, observasi, dokumen, dan pustaka. Temuan penelitian ini menunjukkan sistem pengelolaan masjid Agung Syuhada Polewali Mandar masih di bawah standar, belum sesuai dengan standar yang diberlakukan oleh Direktorat Urusan Agama Islam dan Syariah. Sedangkan peran dan fungsi yang dimainkan oleh Masjid Agung Syuhada Polewali Mandar hanya sebatas pada pelayanan ibadah rutin, pengajian dasar  secara tradisional, dan pelaksanaan HBI (Hari Besar Islam).